The world is not enough [videorecording (DVD)] - Apted, Michael; Brosnan, Pierce; Marceau, Sophie, 1966-; Carlyle, Robert, 1961-; Richards, Denise, 1971-; Coltrane, Robbie; Dench, Judi, 1934-; Fleming, Ian, 1908-1964 (MGM Home Entertainment ; Distributed by Twentieth Century Fox Home Entertainment, 2008)
After the murder of a Russian oil tycoon, James Bond vows to protect his daughter who's taken over her father's operation.